THE ROLE OF PRAGMATIC COMPETENCE IN TRANSLATION - Khasanova Dilnoza (PEDAGOGS, 2025)
Abstract. Translation is not a mere transference of linguistic elements from one language to another; it is a complex cognitive and communicative activity that requires an in-depth understanding of both linguistic and extralinguistic factors. Among these, pragmatic competence — the ability to comprehend and convey intended meanings within specific contexts — plays a fundamental role. This article explores the concept of pragmatic competence, its components, and how it influences translation accuracy, adequacy, and naturalness. The discussion includes examples from intercultural communication, speech act theory, and real-world translation errors, and emphasizes the importance of pragmatic awareness in both literary and non-literary translation.